Reducing apathy in the face of corrupt behaviour: whistleblowing as an act of ‘Amr bi-l-ma’ruf wa-nahy ‘an al-munkar / Khairunnisa Abd. Samad, Haniza Khalid and Saim Kayadibi. - Abd. Samad, Khairunnisa; Khalid, Haniza; Kayadibi, Saim (Universiti Teknologi Mara Selangor, 2015)
Islam promotes ‘‘amr bi-l-ma’ruf wa-nahy ‘an al-munkar” or ‘enjoining good and forbidding wrong’ as the underlying basis of human social, political and economic interactions and core precursor in maximizing human welfare. However, in the business realm today, individuals tend to operate under the rational (i.e. maximizing welfare) mode, only that the welfare maximized is his alone. To curb this tendency, whistle-blowing provisions have been introduced by more and more institutions as one possible mechanism to deter wrongdoings or corrupt behaviour and guide formal investigations of wrongdoings in corporate or public institutions. Whistle-blowing has an undeniable value within the framework of ‘‘amr bi-l-ma’ruf wa-nahy ‘an al-munkar” in institutional governance, alongside other educational and spiritual enhancement efforts. Many of the problems in private and public institutions in Muslim countries can be prevented if people had acted on their suspicions and prompted the authorities to intervene. While many studies have established the importance of cultural and ethical background in determining whistle-blowing motivations and system, very few specifically whistle-blowing within the Islamic doctrine of ‘‘amr bi-l-ma’ruf wa-nahy ‘an al-munkar” and its implications on whistleblowing systems. This paper attempts to fill this void by drawing from elements of the Islamic hisbah system as outlined by Imam al-Ghazali (d. 505H) specifically that can be used to guide drafting of whistle-blowing systems generally. An implication for modern-day managers is that additional investment should ideally be made to leverage on religious feelings and God-consciousness with respect to individual role in enjoining good and forbidding wrong.